Tuntas Cepat Masalah Stunting Sejak Dini Bersama Mahasiswa KUKERTA UNRI 2023 di Desa Sukadamai Singingi Hilir Kuantan Singingi - Viony Syafitra; Inggrid Nikita Bella; Ayasmin Zabrina Ramidil; Bima Abhista Fadhil; Joice Esra Rappita Purba; Karen Arieza Bernanda; Michi Aminatin Rhohmah; Muhammad Hafzul Haikal; Rahmatus Sya’ban Luhur Istigfarin; Sona Greti Aritonang; Tamara Geraldina Pricillia (Universitas Dehasen Bengkulu, 2023)
Stunting is a serious problem of malnutrition that interferes with the growth and development of children. Many factors can cause stunting in toddlers such as toddler characteristics and socioeconomic factors. Stunting can occur before giving birth and is caused by very poor nutritional intake during pregnancy, low quality of life in line with the frequency of communication diseases, thereby inhibiting growth. This observational research was conducted in Sukadamai Village, Singingi Hilir District, Kuantan Singingi District. There is a lack of knowledge among village residents about stunting, therefore KUKERTA UNRI students are embracing residents again in stunting prevention outreach activities. This activity contains appeals for the prevention and proper handling of stunting. Then the impact of the gap that occurs if you don't adopt a healthy and clean lifestyle which can cause stunting in children. The activity continued with the provision of morning exercises and education on a culture of healthy living and nutrition for pregnant women. From this activity, the results and targets that KKN students want to achieve are high enthusiasm from the residents so that this outreach activity runs smoothly. The villagers no longer feel out of place and know about how to prevent stunting. As well as, appropriate complementary feeding of ASI.